The Employment Effects of Ethnic Politics - Francesco Amodio; Giorgio Chiovelli; Sebastian Hohmann (Institute of Labor Economics (IZA), 2019)
This paper studies the labor market consequences of ethnic politics in African democracies. We combine geo-referenced data from 15 countries, 32 parliamentary elections, 62 political parties, 243 ethnic groups, 2,200 electoral constituencies, and 400,000 individuals. We implement a regression discontinuity design that compares individuals from ethnicities connected to parties at the margin of electing a local representative in the national parliament. We find that having a local ethnic politician in parliament increases the likelihood of being employed by 2-3 percentage points. We hypothesize that this effect originates from strategic interactions between ethnic politicians and traditional leaders, the latter retaining the power to allocate land and agricultural jobs in exchange for votes. The available evidence supports this hypothesis. First, the employment effect is concentrated in the historical homelands of ethnicities with strong pre-colonial institutions. Second, individuals from connected ethnicities are more likely to be employed in agriculture, and in those countries where customary land tenure is officially recognized by national legislation. Third, they are also more likely to identify traditional leaders as partisan, and as being mainly responsible for the allocation of land. Evidence shows that ethnic politics shapes the distribution of productive resources across sectors and ethnic groups.
Keywords: J15; J70; O10; P26; Q15; 330; ethnic politics; employment; democracy; traditional leaders; Africa